2009
DOI: 10.1039/b906831g
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly(ethylene terephthalate) using ionic liquids

Abstract: The degradation of poly(ethylene terephthalate) (PET) was successfully achieved using ionic liquids. The products were separated according to their solubilities in boiling water. Average molecular weights of the main product were determined by gel permeation chromatography (GPC). The physicochemical properties of the product have been characterized by scanning electron microscopy equipped with an energy dispersive X-ray analyzer (SEM/EDX), X-ray diffractometer, infrared spectrometric analyzer, differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(136 citation statements)
references
References 26 publications
2
128
0
1
Order By: Relevance
“…Solvolysis processes using water, methanol and glycol can be used to gain terephthalic acid [5][6][7][8][9], dimethyl terephthalate (DMT) [10,11], bishydroxyethyl-terephthalate (BHET) [12][13][14] and glycol from bottle PET, which has a high purity. It may well prove possible to make use of ionic liquids as an alternative for the depolymerisation of PET [15]. Any of the products recovered can be employed in the production of new PET.…”
Section: Introductionmentioning
confidence: 98%
“…Solvolysis processes using water, methanol and glycol can be used to gain terephthalic acid [5][6][7][8][9], dimethyl terephthalate (DMT) [10,11], bishydroxyethyl-terephthalate (BHET) [12][13][14] and glycol from bottle PET, which has a high purity. It may well prove possible to make use of ionic liquids as an alternative for the depolymerisation of PET [15]. Any of the products recovered can be employed in the production of new PET.…”
Section: Introductionmentioning
confidence: 98%
“…It has not been long since ionic liquids were applied as catalyst for PET glycolysis when Wang et al initiated the study and first reported its use in 2009 (Wang et al, 2009a). The main advantage of ionic liquids over conventional catalysts like metal acetates is that the purification of the glycolysis products is simpler.…”
Section: Recyclable Catalyst: Ionic Liquidsmentioning
confidence: 99%
“…It has been reported that ionic liquids were used as solvents and/or catalysts in polymer depolymerization [11,12]. In 2009, Wang [13] found that ionic liquids could catalyze the depolymerization of PET in ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%